Dynamic Interactions Between Stock Returns, Domestic Product and Interest Rates: Evidence from Poland - Pietraszewski, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The paper investigates the relationships between stock returns (represented by changes in the main stock index quoted on Warsaw Stock Exchange, WIG) and changes in Gross Domestic Product, as well as changes in long‑term and short‑term interest rates in Poland over the years 2001–2016. Quarterly data is examined applying time series econometric methods, allowing to take into account the existence of autocorrelation. The results suggest that stock returns lead and can forecast future economic growth. They also point to statistically significant but rather moderate inverse relationship between stock returns and current movements in interest rates, mainly long‑term. These results are consistent with the theoretical arguments in finance and economics.